An Assessment Of Currency Exposure Of Non-financial Firms In Asean-4: Insights Using The Stock Returns And Cash Flow Methodologies - Hishamuddin Abdul Wahab; Norhazlina Ibrahim; Obiyathulla Ismath Bacha; Ahmad Monir Abdullah; Nurul Afaaf Mohd Nasir (AESS Publication, 2024)
Indexed by Scopus/ERA